Quantitative Accuracy Of Different Single Photon Emission Computed Tomography/Computed Tomography (Spect/Ct) Systems With Phantoms Using Tc-99m And I-131 - Al-Qinnah, Moayed Yousef Hasan (2023)
This project aimed to evaluate the performance of three SPECT/CT systems installed at three centres: the Advanced Medical and Dental Institute (AMDIUSM), Hospital Universiti Sains Malaysia (HUSM), and Penang General Hospital (PGH), and to assess levels of error in the quantitation of activity at the centres involved. Furthermore, the aim is to evaluate the stability of the calibration factor of the SPECT/CT system at AMDI over a six-month period.